N+V complex predicates in Guinean Kpelle: Nominal boundedness and bracketing structure - Konoshenko, Maria; Uvarova, Maria (Mandenkan, 2025)
The paper focuses on noun-based complex predicates (NVCPs) in Guinean Kpelle (iso 639-3 [gkp], Southwestern Mande). We explore the degree of nominal boundedness and the bracketing within complex predicates by looking at the phonological, morphological, semantic and syntactic patterning of nouns within NVCPs, based on elicitation data from three speakers. We argue that NVCP nouns form a hierarchy of boundedness: non-spatial nouns > body part names > preverbal nouns; however, due to predicate-specific variability, an overarching syntactic analysis remains impossible. We provide a detailed description of how Guinean Kpelle NVCPs function in the so-called ‘split predicate’ constructions, featuring a systematic mismatch between their syntactic structure and semantic interpretation. Our findings suggest that certain NVCP features in Guinean Kpelle – such as the existence of distinct noun-based NVCP types – align more closely with patterns observed in other languages of Western Mande branch, to which Guinean Kpelle is genetically affiliated. However, other features – like the notably strong autonomy of nominal elements within NVCPs – suggest affinities with Southern Mande languages, reflecting Guinean Kpelle's geographical proximity to that group.